Social factors affecting the utilization of maternal health care services among Dalit women of Kapilvastu municipality - 7, Kapilvastu district. - Pathak, Srijana (2011)
ABSTRACT: Introduction: The study was carried out among the Dalit women living in Kapilvastu Municipality-7. The main aim of the study was to identify the status of utilization of maternal health care services and the social factors that affect in the utilization. Methods: This is a cross-sectional descriptive study. Data was collected from all the 76 women having children upto 1 year of age. Structured questionnaires were used for interview. Results: Of the 42 who had age at marriage of less than 15 years, 90.5% were illiterate showing that the lower the educational level, the lower is the age at marriage. Of 8 respondents who had first child birth at the age below 15 year, all of them were illiterate. Of 8 husbands whose wife had first child birth at the age less than 15 years, 87.5% were illiterate. A huge majority had taken ANC services during their last pregnancy. Most of the respondents (93.9%) went to government district hospital for ANC checkup and the health workers mostly preferred were nurses. Majority of the women had their weight taken during their pregnancy. Of the 55 who had taken TT vaccine during their last pregnancy, 72.7% had taken it twice. Of the 44 who took less food than usual during pregnancy, 95.5% were illiterate. Of 30 who had received PNC services. 43.3% had received it after third day of delivery. Fifty percent of both labors and housewives did not take nutritious food after delivery. Most of the respondents (40%) did not know that an improved diet was needed after delivery, some 20% said that they had less amount of food available in home as the reason for taking low diet. conclusion: Education of the women and their husbands, the occupation they rely on, the economic condition of the women, the gender of the health worker/health service provider affect in the utilization of the maternal health care services of the Dalit women in Kapilvastu Municipality. Keywords: Maternal health care, utilization, ANC, care during delivery, PNC, education, occupation